Segmental evaluation of right ventricular systolic function in atrial septal defect (ASD) type II patients. (14th October 2021) - Rafouli-Stergiou, P; Hiraoka, A; Symons, R; Bogaert, J A; Morais, P; Van De Bruaene, A; Budts, W; Bogaert, J
Abstract: Introduction: A left to right (LR) shunt in atrial septal defect (ASD) may cause right heart and pulmonary overfilling, at the expense of the systemic circulation. Purpose: The study objective was to evaluate the impact of LR shunt on left (LV) and right ventricular (RV) filling, function, and myocardial strain by using cardiovascular magnetic resonance imaging (CMR). Methods: Thirty-five ASD type secundum patients (42±18 y.o.) were compared to a control group (n=40). Cine imaging was used to calculate ventricular volumes and ejection fraction (EF), global longitudinal (GLS) and circumferential (GCS), free wall (FW) and interventricular septal (IVS) longitudinal strain. Phase-contrast imaging was used to calculate pulmonary flow to systemic flow ratio (Qp/Qs). Results: Qp/Qs was 2.2±0.60 (range 1.3–3.6), which resulted in higher RV end-diastolic volume/BSA (EDVi, 152±42 vs. 82±11 ml/m 2 ), lower LV EDVi (72±17 vs. 83±10 ml/m 2 ), and higher RV/LV EDVi ratio (2.1±0.5 vs. 1±0.1) compared to controls (all p<0.001) [Figure 1]. Patients also presented with higher RV, but lower LV indexed stroke volumes (both p<0.001), and a strong trend toward lower RVEF (p=0.08). They demonstrated significantly lower RV GLS (p=0.03) and longitudinal IVS strain (p<0.001) [Figure 2]. RV FW strain or RV GCS did not differ among study groups. Shunt severity correlated with RV size and stroke volume, right atrial size and pulmonary trunk diameter (all p<0.001). In contrast, no correlation was identified with functional nor strain parameters. Conclusion: Cardiac remodeling in ASD patients with long-standing LR shunt negatively affects RV systolic performance, which is likely related to longitudinal septal dysfunction. Funding Acknowledgement: Type of funding sources: None.